2022
DOI: 10.3390/ph15060761
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Dose Intravenous Administration of Neutral and Cationic Liposomes in Mice: An Extensive Toxicity Study

Abstract: Liposomes are widely used as delivery systems for therapeutic purposes. However, the toxicity associated with the multi-dose administration of these nanoparticles is not fully elucidated. Here, we evaluated the toxicity of the prolonged administration of liposomes composed of neutral or cationic phospholipids often used in drug and gene delivery. For that purpose, adult wild-type mice (C57Bl6) were randomly distributed into three groups receiving either vehicle (PBS), neutral, or cationic liposomes and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Therefore, unloaded and GA-loaded liposomes were produced using distinct techniques, including lipid film hydration, reverse-phase evaporation, ethanol injection, and ethanol permeabilization, to obtain a formulation with the best physicochemical properties for brain delivery purposes. The liposomes’ composition included DSPC, CHOL, 18:0 PEG2000 PE, and DSPE-PEG2000 amine at a molar ratio of 52:45:3:0.06, which was maintained regardless of the technique since these particular NPs proved to be safe after intravenously administering 10 doses over 3 weeks to adult wild-type mice [ 26 ]. Including PEG in the liposomes composition (stealth liposomes) allows them to become invisible to the MPS, thus increasing the blood-circulation time of the lipid vesicles [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, unloaded and GA-loaded liposomes were produced using distinct techniques, including lipid film hydration, reverse-phase evaporation, ethanol injection, and ethanol permeabilization, to obtain a formulation with the best physicochemical properties for brain delivery purposes. The liposomes’ composition included DSPC, CHOL, 18:0 PEG2000 PE, and DSPE-PEG2000 amine at a molar ratio of 52:45:3:0.06, which was maintained regardless of the technique since these particular NPs proved to be safe after intravenously administering 10 doses over 3 weeks to adult wild-type mice [ 26 ]. Including PEG in the liposomes composition (stealth liposomes) allows them to become invisible to the MPS, thus increasing the blood-circulation time of the lipid vesicles [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dose-dependent toxicity may impede the practical application of cationic liposomes . Numerous animal studies have documented the toxicity associated with the administration of either a few doses or multiple doses of cationic liposomes, as well as their long-term systemic toxicity. , This toxicity can be attributed to the significant positive charge on the carriers’ surface, which electrostatically binds to the negative charge of cell membranes. Moreover, higher dosages of cationic lipids can result in elevated Zeta potentials and subsequently greater cytotoxicity, compromising their efficacy, patient quality of life, and treatment continuity .…”
Section: Introductionmentioning
confidence: 99%
“…19 Andrade et al reported that repeated intravenous administration of cationic liposomes in rodents resulted in a 45% lethality rate compared to neutral liposomes. 18 It is worth noting that this study employed positively charged lipid DOTAP at an even higher concentration (85 mol %) than that used in EndoTAG-1 prescription.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the variety of cationic vesicles described, there is room for innovation considering aspects such as lowering toxicity, introducing stimuli-responsiveness, and preparing single-component vesicles from inexpensive and easily synthesized compounds. As far as toxicity is concerned, this has been an important issue both in cell cultures and in vivo experiments and constitutes a severe drawback for moving into clinical applications of cationic liposomes. …”
Section: Introductionmentioning
confidence: 99%